2010
DOI: 10.2174/092986710791859306
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Complexes: New Tools for Chemotherapy

Abstract: The importance of organometallics can be noticed by their presence in all life organisms. The most known natural organometallic molecule is vitamin B12, a porphyrin containing a cobalt atom, useful for several enzymatic transformations. Based on the remarkable properties of this class of compounds, a new area of medicinal research was developed. Gérard Jaouen was the first to introduce the term of "bioorganometallic chemistry" in 1985 although the first organometallic therapeutical was Salvarsan®, discovered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 162 publications
1
33
0
Order By: Relevance
“…The methoxy groups of 1 also generated a resonance at 57.2 ppm in the 13 C NMR spectrum in acetone-d 6 All complexes were synthesized and tested as racemic mixtures of enantiomers. To demonstrate that the cyclometalated iridium(III) complexes used in this study are substitutionally inert, the stability of the complexes were investigated by 1 complexes were stable in DMSO-d 6 /D 2 O (9:1; 5 mM) at 298 K for at least seven days, as verified by 1 H NMR spectroscopy. Similarly, UV−vis absorption spectroscopy also showed that the complexes were stable in acetonitrile/Tris-HCl buffer/ (8:2; 10 μM) at 298 K for at least 7 days.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The methoxy groups of 1 also generated a resonance at 57.2 ppm in the 13 C NMR spectrum in acetone-d 6 All complexes were synthesized and tested as racemic mixtures of enantiomers. To demonstrate that the cyclometalated iridium(III) complexes used in this study are substitutionally inert, the stability of the complexes were investigated by 1 complexes were stable in DMSO-d 6 /D 2 O (9:1; 5 mM) at 298 K for at least seven days, as verified by 1 H NMR spectroscopy. Similarly, UV−vis absorption spectroscopy also showed that the complexes were stable in acetonitrile/Tris-HCl buffer/ (8:2; 10 μM) at 298 K for at least 7 days.…”
Section: ■ Introductionmentioning
confidence: 99%
“…But the clinical development of new compounds is often been stopped for various reasons: toxicity, chemistry, pharmacology, or economics, and less than one in ten promising molecules that have entered the pipeline reaches the stage of clinical studies. In the mid- 90 s, we extended the strategy developed by Gérard Jaouen (Vessieres et al , 1988) in anticancer therapy to antimalarial therapy (see Chavain & Biot, 2010 for review). The main antimalarials in current use (CQ, quinine, mefloquine, artemisinin, atovaquone) were modified by introduction of a ferrocenyl moiety in their chemical structure.…”
Section: The Malaria Problemmentioning
confidence: 99%
“…While it is estimated that about 70% of organic drugs are bioinspired or are derivatives of natural products, 1 putative metal-based drugs are normally synthetic. 13 Reflecting growing interest, reviews are also available describing the development of organometallic compounds as therapeutic agents [14][15][16] and, intriguingly, of metal-organic frameworks (MOFs) which may function as drug carriers, that is a new type of drug delivery system. Despite the dominance of organic molecules in chemotherapy, it is of interest that modern chemotherapy is widely acknowledged to have begun with the work of Paul Ehrlich who investigated the efficacy of arsenic compounds for the treatment of, for example, African trypanosominasis.…”
Section: Introductionmentioning
confidence: 99%